Assessment of Anxiety Induced By Bullying Among BS Nursing Students - Muhammad Sajjad Haider; Airsh Amin; Jerry Zahid; Faisal Nadeem; Warda Tu Nisa; Shabana Yousaf Benjamin; Swara Mushtaq (Research Journal of Psychology, 2025)
Introduction: In nursing education, bullying is a persistent problem that causes a negative impact on students’ mental health, which can lead to emotional embarrassment, anxiety, and deprived academic performance. Aim: To assess the level of anxiety caused by bullying among BS nursing students in Rashid Latif Nursing College, Lahore. Method: This study utilized a correlational study design, and 135 students were selected using a simple random technique. There are two adopted scales used (a 30-item bullying questionnaire and a 7-item GAD-7 anxiety scale) to collect data from BS nursing students. The results analyzed through descriptive and inferential statistics. Results: The results of this study exposed that 80% of BS nursing students had mild to severe anxiety symptoms, and 68.8% of BS nursing students reported having been bullied. There was a significant positive correlation between the anxiety and bullying (r = 0.334, p < 0.01). Conclusion: This study found that there is a strong positive correlation between anxiety and bullying in BS nursing students. This study highlights the need for mental health treatments, awareness initiatives, and institutional policies to promote a safe and healthy learning environment.